Vállalatközi konfliktusok és megoldási módszerek: Egy interjús kutatás tapasztalatai (Szociológiai Szemle, 2024)
This study describes the experiences of an interview-based research. This aimed to reveal the different types of conflicts occurring in vendor–debtor relationships and the different solutions to such conflicts. We did not target to draw a representative picture, we only wanted to explore the different types existing. First of all, we wanted to answer, in general, the following question: Are there any market relationships in the Hungarian economy, that enable the use of the methods of constructive conflict handling, i.e. What kind of relationships do exist between the size and form of the interdependence and the solutions given to the different conflicts? The main conclusion of our research was that there are cooperation forms and interdependence situations in the Hungarian vendor–debtor relationships whereby in case of conflicts the parties are motivated to achieve a resolution, therefore applying the alternative methods in the vertical market relationships could work as an efficient and constructive method.